Shaping applied epidemiology workforce training to strengthen emergency response: a global survey of applied epidemiologists, 2019-2020 - Amy Elizabeth Parry; Martyn D. Kirk; David N. Durrheim; Babatunde Olowokure; Samantha M. Colquhoun; Tambri Housen (BMC, 2021)
Abstract Background Rapid and effective emergency response to address health security relies on a competent and suitably trained local and international workforce. The COVID-19 pandemic has highlighted that the health security workforce needs to be well equipped to tackle current and future challenges. In this study, we explored whether training in applied epidemiology was meeting the current needs of the applied epidemiology workforce. Method We conducted a cross-sectional online survey that was available in English and French. We used purposive and snowballing sampling techniques to identify potential survey respondents. An online social media advertisement campaign was used to disseminate a REDCap survey link between October 2019 and February 2020 through field epidemiology networks. Survey questions included demographic details of participants, along with their technical background, level of formal education, topics studied during epidemiology training, and years of experience as an epidemiologist. We used Pearson Chi-squared (Chi2) to test the difference between categorical variables, and content analysis to evaluate responses to open-ended questions. Results In total, 282 people responded to the survey. Participants had a range of formal public health and epidemiology training backgrounds. Respondents applied epidemiology experience spanned almost 30 years, across 64 countries. Overall, 74% (n = 210) were alumni of Field Epidemiology Training Programs (FETP). Basic outbreak and surveillance training was well reported by respondents, however training in specialised techniques related to emergency response, communication, and leadership was less common. FETP graduates reported higher levels of formal training in all survey topics. Conclusion It is critical for the health security workforce to be well-trained and equipped with skills needed to ensure a rapid and effective response to acute public health events. Leadership, communication, interpersonal skills, and specialist training in emergency response are lacking in current training models. Our study has demonstrated that applied epidemiology workforce training must evolve to remain relevant to current and future public health challenges.